L Laga Pinter as A Learning Media in The Material Rectangle of Student Class VII K SMP Negeri 5 Kendari - Asri Azis (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2020)
The purpose of this research is the use of "smart matches" as an ICT-based learning media is to teach and improve learning outcomes of class VII K students of SMP Negeri 5 Kendari on the material of understanding the types and properties of rectangles. The use of "smart matches" through an action learning improvement in the form of development research. The subject matter of understanding the types and nature of rectangles was carried out during two meetings. At the second meeting, students were given a test question in the form of the description as many as 5 numbers and of the 30 people who were given a test of learning outcomes, there were 26 students (86.7%) who scored ≥ 73 and 4 students (13.2%) scored ˂ 73. In the aspect of student skills, the data obtained were 19 students (63.3%) in the very proficient category, 7 students (23.4%) in the advanced category, 1 student (3.3%) in the less proficient category, and 3 students (10.0%). ) the category is not proficient. Qualitative data, namely the level of student satisfaction with the use of "smart matches" in the learning process obtained data as many as 25 students (83.3%) with very good criteria, 3 students (10.0%) with good criteria, 2 students (6.7 %) with unfavorable criteria and no student stated that they were not good. The practicality of the "smart fight" against students can be shown by the practicality value of 78 with a practical assessment. The results showed that the use of "smart matches" as a medium of learning in the material of understanding the types and properties of rectangles can teach and improve the learning outcomes of class VII K students of SMP Negeri 5 Kendari.